2010
DOI: 10.1021/cm102155m
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X-ray Absorption Near-Edge Structure Spectroscopy of ZnO Nanowire Growth During Chemical Bath Deposition

Abstract: Chemical bath deposition (CBD) offers a simple and inexpensive route to deposit semiconductor nanostructures, but lack of fundamental understanding and control of the underlying chemistry has limited its versatility. Here we report the first use of in situ X-ray absorption spectroscopy during CBD, enabling detailed investigation of both reaction mechanisms and kinetics of ZnO nanowire growth from zinc nitrate and hexamethylenetetramine (HMTA) precursors. Time-resolved X-ray absorption near-edge structure (XANE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 50 publications
5
66
0
1
Order By: Relevance
“…Since HMTA does not bind with Zn 2+ ion in the bath, 13 HMTA may be involved in the transition state of the Zn-TAA reaction or directly with the decomposition of TAA. A comprehensive study on the possible reaction pathways of TAA was discussed by Bayoń et al 35 for deposition of In(OH) x S y .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since HMTA does not bind with Zn 2+ ion in the bath, 13 HMTA may be involved in the transition state of the Zn-TAA reaction or directly with the decomposition of TAA. A comprehensive study on the possible reaction pathways of TAA was discussed by Bayoń et al 35 for deposition of In(OH) x S y .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We have previously shown that HMTA does not complex with Zn, and addition of HMTA should not reduce the free Zn 2+ ion concentration. 13 Instead, addition of HMTA should significantly increase the deposition rate by maintaining moderate pH to provide rapid and continual nucleation followed by accelerated growth. We deposited Zn(S,O,OH) thin films by CBD with HMTA as an additive (HMTA films) and compared them to standard films without the bath additive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] 그러나, 벌크재 료의 UV 여기발광(UV stimulated emission) 및 레이저 특성은 저온에서 관찰되므로, 상온에서 UV 여기발광특 성을 관찰하기 위해서는 크기효과(size effect)에 따른 양 자구속효과(quantum confinement effect)를 가질 수 있는 1차원 나노구조가 요구된다. …”
Section: 서 론unclassified
“…[18][19][20] In this work, we compare the behavior of complexing agents by using a reference recipe that we recently developed for rapid deposition of low-oxygen ZnS films for photovoltaic buffer layer and nucleation layer applications. 20 The near-neutral chemistry has a different dominant deposition pathway than the typical ion reaction as described above, but the conclusions can be extended to any system that ions, 23 and thus does not complicate the modeling of speciation. Hence, the important concentrations in our comparison of complexing agents on the deposition rate are the total and free Zn 2+ ion concentrations, TAA concentration, and pH.…”
Section: Introductionmentioning
confidence: 99%